The cytosolic or the mitochondrial glutathione peroxidase-type tryparedoxin peroxidase is sufficient to protect procyclic Trypanosoma brucei from iron-mediated mitochondrial damage and lysis - Schaffroth, Corinna; Bogacz, Marta; Dirdjaja, Natalie; Nißen, Amrei; Krauth-Siegel, Renate (Molecular microbiology, 2016)
African trypanosomes express three virtually identical glutathione peroxidase (Px)-type enzymes that occur in the cytosol (Px I and II) and mitochondrion (Px III) and detoxify fatty acid-derived hydroperoxides. Selective deletion of the genes revealed that procyclic Trypanosoma brucei lacking either the cytosolic or mitochondrial enzyme proliferate nearly as wild-type parasites, whereas the knockout of the complete genomic locus is lethal. Flow cytometry and immunofluorescence analyses revealed that the Px I-III-deficient parasites lose their mitochondrial membrane potential, which is followed by a loss of the lysosomal signal but not the glycosomal one. Mitochondrial damage and cell lysis are prevented by Trolox, ubiquinone derivatives and the iron chelator deferoxamine, whereas starch-deferoxamine is inefficient. In glucose-rich medium, cell death is attenuated suggesting that oxidants generated by the respiratory chain contribute to the lethal phenotype. Thus, the Px-type peroxidases protect procyclic cells from an iron-mediated oxidative membrane damage that originates at the mitochondrion. This contrasts with the situation in bloodstream cells, where the lysosome is the primarily affected organelle. Strikingly, either the cytosolic or the mitochondrial form of the peroxidases is required and sufficient to protect the mitochondrion and prevent cell lysis.
First published: 16 September 2015
Gesehen am 12.05.2020